Reflex Atrioventricular Block - Sutton, Richard (Frontiers in Cardiovascular Medicine, 2020)
Reflex atrioventricular block is well-recorded although it is considered rare. Recent data suggests that it is less rare than has been supposed. It has been shown to occur in both vasovagal and carotid sinus reflexes. It has to be distinguished from paroxysmal atrioventricular block due to ventricular conduction tissue disease. Low chronic adenosine levels combined with adenosine release may mimic reflex atrioventricular block. Explanations of the mechanism of these phenomena have been lacking until the recent past. The relevance of reflex atrioventricular block to clinical decision-making is as a possible indication for pacing the heart with consideration given to the vasodepressor component of the reflex.